Why Benefitting a Person Cannot Constitute a Form of Discrimination. (15th February 2022) - Statman, Daniel
Abstract: The purpose of this article is to discuss whether a person can be discriminated against by means of an action intended to benefit him or her. The discussion is triggered by a recent court decision according to which women may be entitled to compensation for a policy that made them better off in some respect because of its assumed effect on the perpetuation of harmful stereotypes about women. I reject this view, arguing that such effects are neither necessary nor sufficient for an act to be discriminatory. If people stand to directly benefit from some act, they cannot claim discrimination on the basis of such benefit.